2-Methylpyridinium Based Surfactants: Synthesis, Characterization and Potential Application as Drug Carrier Systems: Synthesis of 2-Methylpyridinium Based Surfactants - Fayyaz, Summaira; Talat, Rabia; Ali, Saqib; Khalid, Nasir; Shah, Afzal; Ullah, Faizan; Haider, Ali (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
New cationic surfactants i.e., n-hexyl-2-methylpyridium bromide (a6), n-heptyl-2-methylpyridium bromide (a7) and n-octyl-2-methylpyridium bromide (a8) have been synthesized and characterized by multinuclear (1H, 13C) Nuclear magnetic resonance (NMR) and Fourier-transform infrared spectroscopy (FTIR) spectroscopy. Critical micelle concentration (CMC) values of these compounds were studied in ethanol using conductometric and UV-Visible spectroscopic methods. Dependence of CMC of synthesized surfactants on temperature was used as a parameter to determine the thermodynamic parameters (ΔG, ΔH and ΔS) of micellization process. The negative values of ΔG and positive values of ΔH indicated the spontaneous and endothermic nature of micellization process, respectively. Bioactivity tests of these surfactants showed them as significant biological active compounds. The interaction of drugs (Flurbiprofen and Ketoprofen) with these compounds has been studied by employing UV-Visible spectroscopic method. The binding constant (Kb) and number of drug molecules incorporated per micelle (n) gives evidence of strong interaction of selected drugs with these synthesized surfactants. Negative value of Gibb’s free energy calculated from (Kb) showed the spontaneous nature of drug surfactant interaction.